Association between Probable Generalized Anxiety Disorder with The Planning or Acceptance of The Pregnancy From The Beginning in Women Undergoing Prenatal Care (2023)
Objective: To identify the frequency of Probable Generalized Anxiety Disorder (PGAD) and estimate its association with pregnancy planning or with its acceptance from the beginning. Methods: Cross-sectional study. Pregnant women who attended prenatal consultation, >12 weeks of gestation and without acute morbidity were included. They were asked about pregnancy planning and acceptance from the beginning. They answered the Generalized Anxiety Disorder Questionnaire to identify PGAD. Anonymous and voluntary participation. Results: 702 pregnant women were assessed. Age 28.0±5.7y, gestational age 24.5±10.3w. Preconception consultation 22.8%; planned pregnancy 58.7%, accepted from the beginning 94.3% and PGAD 21.3%. Unplanned pregnancy was more frequent in pregnant women with PGAD than among those without PGAD, 53.4% vs. 38.1% The same was true for the pregnancy not accepted from the beginning, 11.4% vs. 6.3% Pregnancy planned and accepted from the beginning, they were associated with PGAD. OR:0.34[CI95%:0.17-0.67] and OR:0.53[CI95%:0.36-0.77]. Discussion: PGAD was identified in one fifth of the pregnant women. Pregnancy planned and accepted from the beginning, were associated with 66% and 47% lower chance of PGAD. Unplanned or unaccepted pregnancy from the beginning can have a negative impact on mental health. It is suggested to explore mental health and planning/acceptance of the pregnancy, during prenatal control